Peran Pemerintah Desa Glagahwangi Sugihwaras Bojonegoro dalam Pembangunan Desa Perspektif Fiqh Siyasah - Kurniawan, Muchamad Mirsa (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2016)
Abstract: the role of village administration of Gagahwangi Sugihwaras Bojonegoro in implementing the village programs is discussed in this article from the perspective of Islamic political science. The performance of village administration is based on the Law 6/2014 on Village which distributes the village administration between village head and village consultative body. In Glagahwangi, it turns out that the role of village head is more dominant than Village consultative body. Villagers directly delivers their aspiration to village head who is proven to accommodate their aspiration. Whereas Village consultative body is only important in proposing the village head, forming village head election and formulating its statutes. From Islamic political science, the village administration of Glagahwangi has performed its duty to realize villagers’ good and to ensure the order for the profane and religious affairs, therefore it is similar to the concept of ahl al-hall wa al-‘aqd. Keywords: Village administration, village programs, Islamic political science. Abstrak: Artikel ini membahas tentang peran pemerintah desa Glagahwangi Sugihwaras Bojonegoro dalam pelaksanaan pembangunan desa perspektif fiqh siyâsah. Kinerja pemerintah desa Glagahwangi Sugihwaras Bojonegoro didasarkan pada Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Dalam pelaksanaan pembangunan desa, peran kepala desa masih lebih dominan dibanding Badan Permusyawaratan Desa. Kebanyakan masyarakat menyampaikan aspirasinya kepada kepala desa yang dinilai proaktif dan mampu mengakomodasi aspirasi masyarakat. Adapun Badan Permusyawaratan Desa Glagahwangi bertugas mengusulkan pengangkatan kepala desa ketika akan habis masa jabatannya, membentuk panitia pemilihan kepala desa, dan menyusun tata tertib BPD. Dalam perspektif fiqh siyâsah, peran pemerintah desa Glagahwangi Sugihwaras Bojonegoro telah menjalankan tugas untuk mewujudkan kemaslahatan rakyat, menjamin ketertiban urusan dunia dan urusan agama, sesuai dengan konsep imâmah dan ahl al-hall wa al-‘aqd. Kata Kunci: Pemerintah desa, pembangunan desa, fiqh siyâsah.